Antimicrobial and Cytotoxic Potential of Barringtonia asiatica Seed Extracts: A Multi-Assay Approach - Mara, Joy Marie; Anselmo, Charlie (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to evaluate the phytochemical constituents, antimicrobial activities, and cytotoxicity of Barringtonia asiatica seed extract. Phytochemical analysis revealed the presence of alkaloids, saponins, tannins, cardiac glycosides, and flavonoids in both aqueous and ethanol extracts, with terpenoids and steroids present only in the ethanol extract. Antibacterial assays showed that both extracts exhibited resistance against Escherichia coli and Staphylococcus aureus, with streptomycin being the most effective treatment. Antifungal assays demonstrated that commercial fungicides were the most effective against Fusarium verticillioides and Aspergillus niger, followed by B. asiatica ethanol and aqueous extracts. Cytotoxicity tests using brine shrimp lethality assay revealed that B. asiatica ethanol and aqueous extracts were highly toxic, with LC50 values of 24.55 ppm and 181.97 ppm, respectively. The presence of terpenoids, cardiac glycosides, and saponins may contribute to their cytotoxic effects. These findings suggest that B. asiatica seed extracts contain phytochemicals with potential antimicrobial and cytotoxic properties, warranting further drug discovery and development research.